Implementation of Office Management Science in Facing the Digital Business World - Windari, Windari; Annam, Rahmad; Wandisyah R Hutagalung, Muhammad (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2023)
This study aims to find out how to apply office management science and Kendal obstacles faced in the application of office management science. Problem Formulation and Research methods used are collecting data through book references, and Data collection techniques carried out are studying teaching materials about office management science. In the industrial era 4.0, the most important way is to understand the functions of office management science, namely POAC (planning, organizing, actuacting, controlling), these functions can be used as indicators of change in this digital business world. In addition, the obstacles faced due to lack of human resources and lack of understanding of knowledge make it an obstacle to the continuity of the process of implementing office management in digital business.